(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
This paper uncovers both Ghanaian and the Chinese various traditional dances in as much as multicultural comprehension is concerned. There is no denying of the fact that, China has a lot of rich and genealogical traditional dances as applicable to Ghana. Both countries have a peculiar historical traditional ways of doing things most especially dancing, in so far as their respective jurisdictions are concerned. Traditional dancing is not left out of the witness box when accounting for the genealogical analysis on both China and Ghana. Gone were the days when traditional dancing brings people together as one and also even provides a platform for people in meeting their life partners. This handful significance is still in existence.